Commencement of Bankruptcy Proceedings in China - Wu, Weijing (Victoria University of Wellington Law Review, 2004)
Recent events and developments in China’s economic reform have exposed the inadequacy of China’s bankruptcy infrastructure. In this context, a new People’s Republic of China (PRC) bankruptcy law has been proposed. This essay examines the problems in the most recent draft pertaining to the initiation of bankruptcy proceedings. In contrast with the bankruptcy laws of the United States and France, China’s draft presents ambiguities and imperfections in the threshold requirement. Accordingly, further improvements have been proposed to facilitate the commencement of bankruptcy proceedings in the PRC.